Book Reviews. Issue 3 (1st December 2017) - Graziano, John; Cooper, Tom; Marshall, Elsa
The Yeoman of the Guard, Arthur Sullivan, Critical Edition, Colin Jagger (ed.) (2016)Oxford: Oxford University Press, 456 pp., ISBN: 9780193413139, p/bk, £67.50Actor-Musicianship, Jeremy Harrison (2016)London: Bloomsbury Methuen Drama, 220 pp., ISBN: 9781472509635, p/bk, £21.99New York City and the Hollywood Musical: Dancing in the Streets, Martha Shearer (2016)London: Palgrave Macmillan, 230 pp., ISBN: 9781137569370, h/bk, £67.99